Transcanal endoscopic myringoplasty: a retrospective study - Gupta, Anchal; Jamwal, Padam Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Transcanal myringoplasty has the advantages of demanding lower operative time and minimal external incisions. It can be performed using the microscopic or endoscopic approach. Methods: This retrospective study was conducted in the Department of ENT and Head and Neck Surgery, SMGS Hospital, Jammu from January 2018 to January 2020. Patients attending ENT OPD with central dry perforation of tympanic membrane were selected for endoscopic transcanal myringoplasty. Written and Informed consent were taken. During surgery, various parameters were noted including duration of surgery and hospitalization. These patients were followed through a period of 6 months and assessed using pure tone audiometry and graft uptake was seen. Results: Out of 40 patients, male: female ratio was 1.2:1. Time taken for surgery was less than 60 minutes in 16 (40%) patients whereas in 24 (60%) patients it was between 60-120 minutes. In our study the patients with small perforation had excellent graft uptake rates (18/19 patients, 94.73%), whereas patients with medium sized perforation showed graft uptake rate of 76.47% (13/17 patients). Objective analysis of cosmetic result was done at the end of six month and revealed that none of the patient had visible scar. Mean pre-operative air bone gap was 24.38 dB whereas mean postoperative air bone gap was 8.34 dB. Mean improvement comes out to be 16.04 dB. Conclusions: Endoscopic myringoplasty was found to be equally effective, less morbid and very cost effective in small central perforations.